Phonetics Speech Pattern Of 4-Year-Old Child: Dysarthria Study - Mega Witjaksana; Sholihatul Hamidah Daulay (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Language skills is an important component of the human ability as a tool to communicate starting from the age of children and adulthood. However, when a child experiences a language disorders, it will have an impact on his growth and development. The language disorders can be in the form of difficulty in pronouncing several words in forming words so that the word has a different pronunciation from the original, which is called dysarthria. The aim of this study was to determine dysarthria language disorders of 4 years old child in terms of phonetic speech pattern aspects, including vowels, consonants, and diphthongs. In addition, this research was also to assist parents in monitoring their children's language growth. Descriptive qualitative method was used in this study to examine the phonetics speech pattern in language disorders. The participant of this study were 4-year-old-child, observations and interviews of children and mother were conducted to obtain the necessary data. The findings of this study there are 5 words that are incorrect in pronouncing vowels which consist of 3 types of vowels changes, namely vowels “u” to “o”, “e” to “i”, “a” to “e”, and then, there are 22 words that are incorrect in pronouncing consonants which consist of 4 types of consonants changes, namely consonants “r” to “l”, “s” to “c”, “l” to “y”, “k” to “t”, and last, there are 9 words that are incorrect in pronouncing diphthongs which consist of 5 types of diphthongs changes, namely diphthongs “au” to “wu”, “ai” to “e”, “au” to “o”, “ua” to “uw”, and “ia” to “e”.